Intolerance of uncertainty in emotional disorders: What uncertainties remain? - Shihata, Sarah; McEvoy, Peter; Mullan, Barbara; Carleton, R. (Pergamon, 2016)
The current paper presents a future research agenda for intolerance of uncertainty (IU), which is a transdiagnostic risk and maintaining factor for emotional disorders. In light of the accumulating interest and promising research on IU, it is timely to emphasize the theoretical and therapeutic significance of IU, as well as to highlight what remains unknown about IU across areas such as development, assessment, behavior, threat and risk, and relationships to cognitive vulnerability factors and emotional disorders. The present paper was designed to provide a synthesis of what is known and unknown about IU, and, in doing so, proposes broad and novel directions for future research to address the remaining uncertainties in the literature.